Developing policy-relevant river fish monitoring in Greece: Insights from a nation-wide survey - A. N. ECONOMOU; S. ZOGARIS; L. VARDAKAS; N. KOUTSIKOS; Y. CHATZINIKOLAOU; D. KOMMATAS; Y. KAPAKOS; S. GIAKOUMI; E. OIKONOMOU; V. TACHOS (Mediterranean Marine Science, 2016)
A wide-ranging river fish survey was executed in the summer of 2009 as part of the preparatory actions for the establishment of a monitoring programme for the EU Water Framework Directive (WFD). This was the first extensive electrofishing campaign for WFD standardized bioassessment in Greece and the experience and insights gained are used here to provide a review of fish-based assessment conditions and requirements in this country. The survey sampled 85 sites on 25 rivers throughout mainland Greece, collecting 70 species of freshwater fish. Quantitative site-based assemblage data is used for taxonomic and ordination analyses revealing a strong biogeographic regionalization in the distribution of the ichthyofauna. The structural and spatial organisation of the fish fauna through the use of species-level and community-level data analyses is explored in three ecoregions where data was deemed sufficient. Transitions in community taxonomic composition among ecoregions were abrupt and concordant with geographical barriers and reflect the influence of historical biogeographic processes. Community-based analysis revealed a substantial degree of variation in quantitative attributes of the fish assemblages among ecoregions. Key conclusions of this work are: (a) the fish-based bioassessment system must be regionalised to reflect biogeographic variation, (b) high faunal heterogeneity among ecoregions (taxonomic, structural), and to a lower degree among basins, constrain the transferability of bioassessment metrics and indices created for explicit regions to other regional frameworks; (c) faunal depauperation in most of the study areas reduce the utility of functional bioassessment metrics and also limits the utilization of rare species and the applicability of the classical form of the “Index of Biotic Integrity” concept. Recommendations to cope with these problems are discussed.

Risk screening of non‐native, translocated and traded aquarium freshwater fishes in G reece using F ish I nvasiveness S creening K it - C. Perdikaris; N. Koutsikos; L. Vardakas; D. Kommatas; P. Simonović; I. Paschos; V. Detsis; L. Vilizzi; G. H. Copp (Fisheries Management and Ecology, 2016)
The invasion of non‐indigenous freshwater fish species is one of the most important threats to aquatic biodiversity. Similar to other Mediterranean countries, Greece is considered a hot spot for freshwater biodiversity, with many range‐restricted endemics of high conservation concern. The aim of this study was to undertake a risk screening assessment to evaluate the invasive potential of non‐native, translocated and traded aquarium fishes in Greece by applying the Fish Invasiveness Screening Kit ( FISK ). In total, 73 freshwater fish species were evaluated by two assessors. FISK was able to discriminate reliably between invasive and non‐invasive species with a threshold of 15.25. Based on mean scores, 30 species were classified as ‘high risk’, of which 17 as ‘moderately high risk’, six as ‘high risk’ and seven as ‘very high risk’. There was a high coincidence rate for the species categorisation between the two assessors, but significant differences in certainty. The results suggest that FISK is a useful tool for assessing risks posed by non‐native, translocated and traded aquarium fish species in Greece.

Ornamental fish in pet stores in Greece: a threat to biodiversity? - I. PAPAVLASOPOULOU; L. VARDAKAS; C. PERDIKARIS; D. KOMMATAS; I. PASCHOS (Mediterranean Marine Science, 2013)
The aquarium trade has been recognized as an important pathway for the introduction of invasive species around the world. This study investigates the availability of ornamental fish species in ten large-size, centrally positioned aquarium stores that control a large share of imports and the Hellenic market chain, and aims to provide a provisional checklist on the aquarium fish trade in Greece. For each recorded species, additional data concerning various aspects (e.g. natural environment, native range, established as aliens, conservation status and threats to humans) were collected from Fishbase, IUCN red list and the scientific literature. Overall, 326 fish species belonging to 64 families were reported according to the store labels. The majority of the species recorded were freshwater (66%), originating mainly from South America and Asia, while most of the marine species (26%) had primarily an Indo-Pacific native distribution. Among the freshwater fishes, Cichlidae and Cyprinidae were the dominant families with 64 and 27 species, respectively, while the family Acanthuridae dominated within the marine fishes with ten species. The vast majority of both freshwater and marine species (>90%) were tropical. Concerning the presence of alien species, 62 ornamental species have been established outside their natural range, with 22 of them positively confirmed as aliens in the European waters. Moreover, 25 species were listed in the critically endangered (CR), endangered (EN) and vulnerable (VU) categories of the IUCN red list. Even more surprisingly, for 192 species recorded, data were missing to assign their conservation status or had not been assessed at all. Finally, the majority of the species (84%) were harmless to humans. However, 35 species (11%) were recognised as potentially harmful (i.e. venomous, ciguatera poisoning, traumatogenic) and two were found to be poisonous if consumed. In conclusion, the aquarium fish sector in Greece is practically uncontrolled given the presence of: a) threatened species, b) species potentially harmful to humans and c) species capable of establishing non-indigenous populations, if released into the wild.